Cowdung Economy - Sagariya, K. P. (Indian Forester, 1945)
Only a small percentage of the available cowdung is being used as farmyard manure. Large quantities are either not collected or else used as fuel. The main reason for its utilisation as fuel is the non-availability of alternative fuels at cheaper rates, and not the ignorance or the apathy of the people. Under existing conditions when the stock subsists mostly on grazing on poor pastures, the dung must be poorer in nitrogen and phosphorus contents and urine which contains a larger percentage of these nutrltlve elements must remain unutilised. This points to the necessity of stall-feeding the stock on more. Nutritive fodder rich in concentrates, such as oil-cakes and pulses, and production of cheaper nrewood nearer the hearths. This will be ditncult so long as export of charcoal is not restricted and firewood and grass plantations are not created nearer the consuming centres because wood and grass are bulky commodities which cannot be economically transported over long leads. Creation of fodder-cum-fuel reserves dotted all over the intensively-cultivated tracts is thus the prime need. Given the necessary facilities and expert help, there is no reason why the agriculturists themselves should not be able to create such plantations and manage them economically on a co-operative basis.